Social Media and Xenophobic Solidarity in Post-colonial Africa - Godwin Etta Odok (African Human Mobility Review, 2021)
In recent times, there is a resurgence of aggressive consciousness by citizens of most African countries, firmly fashioned and sustained through social media. Social media in this way effectively play roles of mobilizing and (re)constructing national identities and solidarities in ways that citizens regularly enter into violent confrontations with foreign nationals, often stereotyped as threats to the prosperity of citizens. In some African countries, executive orders have been given by heads of government that saw the vicious expulsion of millions of foreign nationals. With the advent of distance-andtime- shrinking information and communication technologies, social media platforms such as Facebook‚ Twitter‚ YouTube and WhatsApp are relied upon in rousing support for national interests and in-group solidarity. Through a systematic review of national immigration policies and content analysis of Facebook newsfeeds in selected countries of East/Central, West and Southern Africa (Zimbabwe, Ethiopia, the Democratic Republic of the Congo (DRC), Nigeria, Somalia, Ghana, Uganda, and South Africa), this paper examines how social media strengthen in-group solidarities with the attendant consequences of loss of lives, properties, and inter-state diplomatic relations in postcolonial Africa. The paper concludes that while encouraging freedom of expression within the continent, social media also bolster freedom to hate as both citizens and foreign nationals become more distrustful of one another, thereby exacerbating competition, rivalry and xenophobia. As citizens exercise their right to voice their opinions, they also actively dehumanize foreign nationals. The paper recommends that kin and friendship networks should become the sphere within which interventions for antixenophobia campaigns occur in post-colonial Africa, as these hold the social capital to bridge the divide between citizens and foreign nationals in attempts to achieve peaceful co-existence.